1997
DOI: 10.1046/j.1365-2486.1997.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil fungal‐arthropod responses to Populus tremuloides grown under enriched atmospheric CO2 under field conditions

Abstract: We investigated the influence of elevated CO2 and soil N availability on the growth of arbuscular mycorrhizal and non‐mycorrhizal fungi, and on the number of mycophagous soil microarthropods associated with the roots of Populus tremuloides. CO2 concentration did not significantly affect percentage infection of Populus roots by mycorrhizal or non‐mycorrhizal fungi. However, the extra‐radical hyphal network was altered both qualitatively and quantitatively, and there was a strong interaction between CO2 and soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 24 publications
4
57
0
Order By: Relevance
“…Klironomos et al (1996) found that exposure of plants to elevated [CO # ] resulted in a shift in the balance between mycorrhizal and nonmycorrhizal fungi and bacteria. They later reported that exposure to elevated [CO # ] resulted in a stimulation of a mycorrhizal-based soil food web when soil N was limiting, and a stimulation of the opportunistic-saprobic\pathogenic-fungus-based food web when N was nonlimiting (Klironomos et al, 1997). The increase in pathogenic fungi in high N could result in more root disease and higher mortality.…”
Section: Effects Of Soil Organisms On Root Longevitymentioning
confidence: 99%
“…Klironomos et al (1996) found that exposure of plants to elevated [CO # ] resulted in a shift in the balance between mycorrhizal and nonmycorrhizal fungi and bacteria. They later reported that exposure to elevated [CO # ] resulted in a stimulation of a mycorrhizal-based soil food web when soil N was limiting, and a stimulation of the opportunistic-saprobic\pathogenic-fungus-based food web when N was nonlimiting (Klironomos et al, 1997). The increase in pathogenic fungi in high N could result in more root disease and higher mortality.…”
Section: Effects Of Soil Organisms On Root Longevitymentioning
confidence: 99%
“…However, studies of AM and plant responses to elevated CO # have shown variable results. Several studies have reported an increase in percent AM fungal colonization and enhanced plant biomass under elevated CO # conditions (Morgan et al, 1994 ;Klironomos, Rillig & Allen, 1996), while other studies have found percent colonization or the plants themselves to be unresponsive to CO # enrichment (Curtis et al, 1994 ;Jongen, Fay & Jones, 1996 ;Klironomos et al, 1997 ;Schenk, Jager & Weigel, 1997). There is also evidence of plant speciesspecific responses to the same AM fungal inoculum under elevated CO # (O' Neill et al, 1991 ;Monz et al, 1994).…”
Section: The Global Rise In Atmospheric Comentioning
confidence: 99%
“…In studies with Artemisia tridentata, Klironomos et al (1996) found that proportions of arbuscules, internal hyphae and external hyphae increased, whereas proportions of vesicles and spores were unresponsive to CO # enrichment. In Populus tremuloides, CO # enrichment caused an increase in extra-radical hyphal length but no change in intra-radical colonization levels (Klironomos et al, 1997). It has been suggested that under conditions of environmental stress, AM fungi will respond by favouring vesicle over arbuscule formation (Duckmanton & Widden, 1994 ;Klironomos et al, 1996).…”
Section: The Global Rise In Atmospheric Comentioning
confidence: 99%
See 2 more Smart Citations